Accounting Rules And Principles In Analysis: a Qualitative Atudy In Tunisia - Jammoussi, Imen; Mroua, Mourad (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
Through this approach, we have sought to know whether compliance with accounting principles is indeed sufficient for the objective of true and fair view to be achieved. In other words, the faithful image of a standardized accounting through the summary statements is an easily achieved objective, notwithstanding the value of the staff and the quality of the management. To circumscribe our approach, and study the effect of compliance with accounting principles on the faithful image, we resorted to semi-structured interviews. The results we have reached reveal that by systematically expressing the facts in financial flows, this leaves out the accounting of very important factors in the life of the company. This is first the quality of its management and then the value of its staff, and more particularly its manager who has more control than the owners themselves on the value of the company and on the risks incurredKeywords: Accounting, rules, accounting principles, faithful image, Tunisia